Proliferaciones algales 2000–2001 en Bahía de Banderas, México según el sensor SeaWiFS - C. Gómez Villareal, María; D. Martínez Gaxiola, Marcos; L. Peña Manjarrez, José (Revista de Biología Tropical, 2008)
Algal blooms for the period of 2000 and 2001 at Banderas Bay, México, were analyzed from SeaWiFS-ocean-color-sensor derived information. These events were related with the maximum chlorophyll week anomalies (ASi; a proxy variable constructed for the analysis of chlorophyll temporal variation in the bay). The winter-spring blooms were multispecific, while the summer-fall blooms were monospecific. Two proposals are made: 1) Winter-spring blooms are strongly related with mesoescale processes, due to their apparent temporal synchrony with the high chlorophyll levels in the coastal region from Sinaloa to Jalisco states; 2) Cochlodinium polykrikoides (Margalef 1961)blooms during the summer-fall periods could be induced by local conditions and the influence of previous events on the ecosystem.